Pengaruh Beban Kerja, Kompetensi dan Red Flags terhadap Kemampuan Auditor Dalam Mendeteksi Kecurangan Laporan Keuangan: Studi Empiris pada Kantor Akuntan Publik di Wilayah Bekasi - Bayu Muktiono; Tri Widyastuti; Pratiwi Nila Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to investigate the influence of workload, competence, and red flags on auditors' ability to detect financial statement fraud. Fraud detection is a crucial aspect of the audit process, especially amidst increasing business complexity and pressure on the integrity of financial reporting. This study was conducted on 104 external auditors working at 12 Public Accounting Firms (KAP) operating in the Bekasi area. Respondents were selected using a purposive sampling technique, namely selecting samples based on certain criteria relevant to the research objectives. Data collection was carried out by distributing questionnaires compiled based on research variable indicators, then analyzed using hypothesis testing with the help of SPSS Statistics software version 26. The results of the analysis indicate that partially, the variables of workload and red flags have a negative influence on auditors' ability to detect financial statement fraud. This indicates that auditors with high workloads or who do not accurately identify red flags have a lower tendency to detect fraud. Conversely, auditor competence shows a significant positive influence on fraud detection ability. Auditors who have adequate knowledge, skills, and experience tend to be more capable of identifying and analyzing indications of fraud in financial statements. Simultaneously, the three independent variables—workload, competence, and red flags—significantly influence auditors' ability to detect financial statement fraud. This finding underscores the importance of managing auditor workload, improving competence through ongoing training, and developing a thorough understanding of red flag indicators to enhance audit effectiveness and financial statement quality. This research is expected to contribute to the development of audit practices and the enhancement of auditor professionalism in Indonesia.